Impact of Cyclosporine Levels on the Development of Acute Graft versus Host Disease after Reduced Intensity Conditioning Allogeneic Stem Cell Transplantation. (30th January 2014) - García Cadenas, Irene; Valcarcel, David; Martino, Rodrigo; Piñana, J. L.; Barba, Pere; Novelli, Silvana; Esquirol, Albert; Garrido, Ana; Saavedra, Silvana; Granell, Miquel; Moreno, Carol; Briones, Javier; et al.
Abstract : We analyze the impact of cyclosporine (CsA) levels in the development of acute graft-versus-host disease (aGVHD) after reduced intensity conditioning allogeneic hematopoietic transplantation (allo-RIC). We retrospectively evaluated 156 consecutive patients who underwent HLA-identical sibling allo-RIC at our institution. CsA median blood levels in the 1st, 2nd, 3rd and 4th weeks after allo-RIC were 134 (range: 10–444), 219 (54–656), 253 (53–910) and 224 (30–699) ng/mL; 60%, 16%, 11% and 17% of the patients had median CsA blood levels below 150 ng/mL during these weeks. 53 patients developed grade 2–4 aGVHD for a cumulative incidence of 45% (95% CI 34–50%) at a median of 42 days. Low CsA levels on the 3rd week and sex-mismatch were associated with the development of GVHD. Risk factors for 1-year NRM and OS were advanced disease status (HR: 2.2, P = 0.02 ) and development of grade 2–4 aGVHD (HR: 2.5, P < 0.01 ), while there was a trend for higher NRM in patients with a low median CsA concentration on the 3rd week (P = 0.06 ). These results emphasize the relevance of sustaining adequate levels of blood CsA by close monitoring and dose adjustments, particularly when engraftment becomes evident. CsA adequate management will impact on long-term outcomes in the allo-RIC setting.